Ղարաբաղի խանության և Օսմանյան կայսրության առնչությունների պատմությունից - Մաղալյան, Արտակ (Մատենադարան)
In their letter dated 29 May 1784 to the Governor-General of the Caucasian Viceroyalty P. S. Potemkin, the Catholicos of Gandzasar Hovhannes Hasan-Jalalyan and the Melik-Princes of Artsakh warned him about the regular visits of the Ottoman Empire’s agents to the Transcaucasian khans and about the encouraging messages of the latter. This important document was written after such significant historical events as the annexation of the Crimea to Russia and the signing of the Georgievsky Treaty on 24 July 1783, according to which the East-Georgian Kingdom came under the patronage of the Russian Empire. According to this Treaty, two battalions of Russian troops under the command of Colonel S. D. Burnashev were to be deployed in Georgia. Католикос Гандзасара Ованес Асан-Джалалян и мелики Арцаха в своем письме от 29 мая 1784 г. к командующему русскими войсками на Северном Кавказе («Кавказской линии») генералу П. С. Потемкину предупреждали его о регулярном посещении агентами Османской империи ханов Закавказья и о получении последними поощрительных посланий. Этот важный документ был написан после таких значимых исторических событий, как присоединение Крыма к России и подписание Георгиевского трактата 24 июля 1783 г., по которому Восточно-Грузинское царство переходило под покровительство Российской империи. Согласно этому трактату, в Грузии должны были дислоцироваться два батальона российских войск под командованием полковника С. Д. Бурнашева.
Keywords: Պատմաբանասիրություն